Adrenal discharge produced by drugs injected into the adrenal - Houssay, Bernardo Alberto (1926)
When studying the effects of nicotin on adrenal secretion it was found that the injection of this drug into the adrenal gland produced a marked increase of the epinephrin secretion. In this paper the effects of several other drugs have been studied by the same method.